2009
DOI: 10.4315/0362-028x-72.4.885
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aflatoxin M1 in Human Breast Milk and Raw Cow's Milk in Istanbul, Turkey

Abstract: This survey was undertaken to determine the extent of aflatoxin M1 (AFM1) contamination in human breast milk and raw cow's milk in Istanbul, Turkey. Samples of human and raw cow's milk were collected randomly and analyzed for AFM1 using an enzyme-linked immunosorbent assay and high-performance liquid chromatography with fluorescence detection in which the samples were cleaned up with immunoaffinity columns. In this study, AFM, was detected in 8 (13.1%) of 61 human breast milk samples examined (mean +/- SD leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Several reports are available wherein AFM1 has been found in milk. It has been detected in breast milk and in cord blood and maternal blood in African countries (like in Sudan, Ghana, and Kenya), the Guangi Xi region of China (Galvano and others 1996), UAE (Abdulrazzaq and others 2003), Turkey (Keskin and others 2009), Australia, and Thailand (El Nezami and others 1995). Also, reports are available on the high contamination of AFM1 in milk in a few EU countries (between 28 and 1012 ng/kg; Markaki and Melissari 1997; Martin and Martin 2000).…”
mentioning
confidence: 99%
“…Several reports are available wherein AFM1 has been found in milk. It has been detected in breast milk and in cord blood and maternal blood in African countries (like in Sudan, Ghana, and Kenya), the Guangi Xi region of China (Galvano and others 1996), UAE (Abdulrazzaq and others 2003), Turkey (Keskin and others 2009), Australia, and Thailand (El Nezami and others 1995). Also, reports are available on the high contamination of AFM1 in milk in a few EU countries (between 28 and 1012 ng/kg; Markaki and Melissari 1997; Martin and Martin 2000).…”
mentioning
confidence: 99%
“…The breast milk samples that contained measurable amounts of AFM 1 (DL ¼ 5 ng/L) in the present study were over these limits. Studies from different cities in Turkey have reported different levels of AFM 1 in breast milk (Altun et al, 2017;Atasever et al, 2014;Dinleyici et al, 2018;Gürbay et al, 2010;Keskin et al, 2009;Ö zdemir & Kuyucuoglu, 2007;Uyar et al, 2014). Numerous studies from Egypt (Polychronaki et al, 2007), Brazil (Iha et al, 2014), Nigeria (Adejumo et al, 2013), Iran (Azarikia et al, 2018;Maleki et al, 2015), Mexico (Cantú-Cornelio et al, 2016), Serbia (Kos et al, 2014), and Portugal (Bogalho et al, 2018) indicate negative health effects for infants related to the presence of AFM 1 in breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…Diet is a primary risk factor for exposure to aflatoxins due to the metabolic processes of mycotoxins and the risk of these poisons accumulating in the adipose tissue and passing into breast milk. Although a number of researchers have reported that there is no significant correlation between AFM 1 levels in breast milk and food the mother consumes (Atasever et al, 2014; Dinleyici et al, 2018;Keskin et al, 2009;Maleki et al, 2015), other studies have shown that peanuts, chili peppers, dried figs, raisins, and other dried fruits as well as corn, wheat, milk, and milk products are foods that are at increased risk of containing aflatoxins (Altun et al, 2017;Cherkani-Hassani et al, 2016;Shuib et al, 2017). Dried fruits and spices may be susceptible to contamination with mold, and therefore to mycotoxins, due to insufficient drying processes or unsuitable storage conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations